2012
DOI: 10.1017/s0305741012000860
|View full text |Cite
|
Sign up to set email alerts
|

Local Energy Efficiency Policy Implementation in China: Bridging the Gap between National Priorities and Local Interests

Abstract: This paper analyses Chinese sub-national governments' implementation strategies to meet national energy efficiency targets in the 11th Five-Year Plan (2006. Previous research has focused on the ways governance practices and decision-making structures shape implementation outcomes, yet very little attention has been given to what strategies local leaders actually employ to bridge national priorities with local interests. To illustrate how local leaders work politically, this paper highlights specific implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 9 publications
0
91
0
Order By: Relevance
“…There is some evidence to support this viewpoint: with regard to the retrofitting of existing buildings, the local government in Changchun changed the voluntary-based subsidy program to an essentially free, but involuntary retrofit program, resulting in the successful retrofitting of a large number of apartments in a very short period [53]. In another illustrative case, officials responsible for implementing the industrial energy-efficiency programs in Shanxi province were able to increase public support and minimize political resistance by policy-bundling: the programs were implemented as part of larger campaigns and connected with policies and concerns of a more local or immediate interest [54]. Furthermore, in Beijing, the government provides additional incentives for purchasing electric vehicles by exempting them from the strict car ownership control program.…”
Section: Flexible Implementationmentioning
confidence: 99%
“…There is some evidence to support this viewpoint: with regard to the retrofitting of existing buildings, the local government in Changchun changed the voluntary-based subsidy program to an essentially free, but involuntary retrofit program, resulting in the successful retrofitting of a large number of apartments in a very short period [53]. In another illustrative case, officials responsible for implementing the industrial energy-efficiency programs in Shanxi province were able to increase public support and minimize political resistance by policy-bundling: the programs were implemented as part of larger campaigns and connected with policies and concerns of a more local or immediate interest [54]. Furthermore, in Beijing, the government provides additional incentives for purchasing electric vehicles by exempting them from the strict car ownership control program.…”
Section: Flexible Implementationmentioning
confidence: 99%
“…Such energy-saving measures included cutting electricity to hospitals, homes, and rural villages. During the last quarter of the 11th FYP, local governments also used "sleeping management" (xiumian guanli ) to temporarily shut energy-intensive companies (Kostka and Hobbs 2012;Harrison and Kostka 2014). Such drastic 11th-hour practices illustrate that some local leaders choose the path of least resistance in selecting short-term, low-quality approaches to satisfying environmental targets and, while nominally following green directives, are actually putting off the difficult business of changing lanes.…”
Section: The Green Implementation Gapmentioning
confidence: 99%
“…Governments are a key driving force of industrial energy conservation (Ke et al, 2012a;Kostka and Hobbs, 2012;Price et al, 2001;Price et al, 2010;Zhao et al, 2014). Tanaka (2011) reviewed over 300 energy efficiency policies worldwide and found that although negotiated agreements are the most common approaches, economic instruments such as carbon tax and emissions trading are increasingly used.…”
Section: Introductionmentioning
confidence: 99%